UMP Gambang Campus closes temporarily from 13 to 26 November - Mimi Rabita, Abdul Wahit (2021)
PAYA BESAR, 13 November 2021 - Universiti Malaysia Pahang (UMP) has temporarily closed all its operations at UMP Gambang Campus to curb the spread of COVID-19, especially on the campus from 13 to 26 November 2021.